IMPLEMENTASI METODE IMPORTANCE PERFORMANCE ANALYSIS DAN WEBQUAL DALAM PENGGUNAAN WEBSITE DIREKTORAT JENDERAL BEA DAN CUKAI - Sri Lestari; Helmida Priandini (CKI ON SPOT, 2018)
The rapid progress of the development of international trade, both concerning activities in the field of import and export, demands a more effective and efficient system and customs procedures and can improve the smooth flow of goods and documents. With the increasing number of international trade players and the development of information technology, the Indonesian Directorate General of Customs and Excise launches an official the new website that aims to publish information relating to the existence of the Indonesian Directorate General of Customs and Excise in a fast, transparent, accurate and service-oriented manner. Regarding strengthening the public relations function in accordance with the development of information technology and the increasingly fast and dynamic needs of the community, in 2017 the website was refined both in terms of layout and information presented as a means of publication, education and services related to customs and excise. The purpose of this study is to examine the relationship between website quality and user satisfaction. From distributing questionnaires, variable testing is done by testing the validity and reliability, data normality and assumption testing as a condition for implementing steps for multiple linear regression analysis. Based on the results of this study, it was found that the variable quality of use (usability), information quality (information quality) and quality of interaction (interaction quality) is quite influential on user satisfaction (website satisfaction) of the Directorate General of Customs and Excise website.